2009
DOI: 10.1007/s10228-009-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

How does shoreline development impact the recruitment patterns of coral reef fish juveniles (Moorea Island, French Polynesia)?

Abstract: The study examined the effects of coastal embankment building on fish recruitment in three habitat types (beach-rock, white sand and muddy sand) in the near shore and fringing reef habitats of Moorea lagoon (French Polynesia). The results showed a positive relationship between the presence of embankments and the density and species richness of juvenile fish along the shoreline (whatever the habitat types). However, embankments deteriorated adjacent fringing reefs (decrease of live coral), which led to a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…; Lecchini et al . ; Benet ). The resident human population has grown from 2000 in 1946 to ~17 000 in 2007 and over this last decade 100 000 tourists have visited per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lecchini et al . ; Benet ). The resident human population has grown from 2000 in 1946 to ~17 000 in 2007 and over this last decade 100 000 tourists have visited per year.…”
Section: Discussionmentioning
confidence: 99%
“…Moorea is the sister island of Tahiti; the two are separated by only 20 km. The coastal marine habitats of Moorea that form the feeding, breeding and nursery areas for blacktip reef sharks (see Mourier & Planes 2013) have been subjected to extensive manipulation and destruction since 1960 (Aubanel et al 1999;Lecchini et al 2009;Benet 2010). The resident human population has grown from 2000 in 1946 tõ 17 000 in 2007 and over this last decade 100 000 tourists have visited per year.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists working in Moorea have highlighted the ecologically detrimental effects of coastal armoring even though there is debate concerning the varying effects different types of infrastructure may have, some showing apparently beneficial impacts on biodiversity. Lecchini et al (2009) showed that coastal embankments in Moorea deteriorated adjacent fringing reefs through habitat loss and decrease of proportion of living corals which, in turn, has led to a decrease of juvenile fish along the coastline. For example, more commercially prized fish (e.g., Mullidae, Mugilidae, Carangidae) were observed near non-armored sandy beaches than in areas located in front of coastal infrastructure.…”
Section: Scientists' and Residents' Perceptions Of The Ecological Imp...mentioning
confidence: 99%
“…Coastlines have been identified as particularly vulnerable environments to the rapid socio-ecological changes occurring in the South Pacific (Madi Moussa et al, 2019). Yet, they provide many essential ecosystem services for humans (e.g., fish nursery areas, marine food resources as well as beaches for various tourismoriented and recreational activities) (Aouiche et al, 2016;Barth et al, 2015;Liquete et al, 2013;Lecchini et al, 2009). The management of this crucial land-sea interface represents an environmental challenge as it is subject to multiple pressures, such as the following: growing beach and soil erosion, public or private coastal artificialization (e.g., landfills, construction of harbors and seawalls), as well as increased release of bio-chemical and non-degradable waste (Defeo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation